A Critical Review of IEC 61850 Testing Tools - Taha Selim Ustun (Sustainability, 2021)
Smartgrid technologies necessitate the use of information technologies (IT) and communication in power system networks. There are different ways of integrating power system equipment in the communication layer for successful information exchange. IEC 61850 offers standard support object-oriented modeling and standardized parameter declaration. This lends itself to the diverse nature of power systems and supports plug-and-play (PnP) operation in smartgrids. Considering the amount of time that is invested in customizing non-PnP communication networks, this is a huge advantage and the main reason behind the popularity of IEC 61850. In line with this popularity, the body of research regarding this standard is constantly growing. In order to test the developed IEC 61850 models and messages, various tools are required. Researchers operate with a limited budget and have to know the abilities and limitations of such tools before making a procurement decision. This paper provides a critical review of IEC 61850 testing tools available in the market. It compares them in terms of their abilities, technical superiority and customer experience, including delivery time and customer support. Researchers in this field will benefit significantly from this work when making procurement decisions based on their needs.